2016
DOI: 10.1002/prot.25042
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants in bacterial 2‐keto‐3‐deoxy‐D‐gluconate dehydrogenase KduD for dual‐coenzyme specificity

Abstract: Short-chain dehydrogenase/reductase (SDR) is distributed in many organisms, from bacteria to humans, and has significant roles in metabolism of carbohydrates, lipids, amino acids, and other biomolecules. An important intermediate in acidic polysaccharide metabolism is 2-keto-3-deoxy-d-gluconate (KDG). Recently, two short and long loops in Sphingomonas KDG-producing SDR enzymes (NADPH-dependent A1-R and NADH-dependent A1-R') involved in alginate metabolism were shown to be crucial for NADPH or NADH coenzyme spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In addition, the molecular surface charge calculated at pH 7.0 shows that the corresponding site is positively charged in A1-R, but slightly negative in A1-R', and this charge may be crucial for the binding or repulsion of the negatively charged NADPH phosphate. These differences in space and charge are caused by two loops, which are referred to as the short and the long loops (A1-R, short loop 13 TGSSQ 17 , long loop 37 HGRKAPA 43 ; A1-R', short loop 13 TGSTE 17 , long loop 37 NSHVDPA 43 ), and the structural features in the two loops are probably important for coenzyme specificity (Figure 6).…”
Section: Molecular Conversion Of Coenzyme Specificity In Deh Reductasementioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the molecular surface charge calculated at pH 7.0 shows that the corresponding site is positively charged in A1-R, but slightly negative in A1-R', and this charge may be crucial for the binding or repulsion of the negatively charged NADPH phosphate. These differences in space and charge are caused by two loops, which are referred to as the short and the long loops (A1-R, short loop 13 TGSSQ 17 , long loop 37 HGRKAPA 43 ; A1-R', short loop 13 TGSTE 17 , long loop 37 NSHVDPA 43 ), and the structural features in the two loops are probably important for coenzyme specificity (Figure 6).…”
Section: Molecular Conversion Of Coenzyme Specificity In Deh Reductasementioning
confidence: 99%
“…Molecules 2022, 27, x FOR PEER REVIEW 10 of 14 charged NADPH phosphate. These differences in space and charge are caused by two loops, which are referred to as the short and the long loops (A1-R, short loop 13 TGSSQ 17 , long loop 37 HGRKAPA 43 ; A1-R', short loop 13 TGSTE 17 , long loop 37 NSHVDPA 43 ), and the structural features in the two loops are probably important for coenzyme specificity (Figure 6). Adaptively evolved yeast (S. cerevisiae) transformed with the A1-R' gene produced the mutant A1-R' with a Glu-to-Gly substitution at position 17 [9] as described below.…”
Section: Molecular Conversion Of Coenzyme Specificity In Deh Reductasementioning
confidence: 99%
See 2 more Smart Citations
“…For example, streptococci distributed in various tissues, such as the oral, gut, and urogenital organs, are known to degrade and/or assimilate HA 19 , 20 , and streptococcal HA lyases release unsaturated HA disaccharides from HA 21 . Previous reports have indicated that unsaturated HA disaccharides are incorporated into bacterial cells by phosphotransferase system (PTS) 22 and degraded and metabolized to glyceraldehyde-3-phosphate and pyruvate by cytoplasmic enzymes 23 25 , such as unsaturated glucuronyl hydrolase (UGL), 4-deoxy- l - threo -5-hexosulose-uronate ketol-isomerase (DhuI), 2-keto-3-deoxy- d -gluconate dehydrogenase (DhuD), 2-keto-3-deoxy- d -gluconate kinase (KdgK), and 2-keto-3-deoxy- d -phosphogluconate aldolase (KdgA; Supplementary Fig. 1 a).…”
Section: Introductionmentioning
confidence: 99%